Pengaruh Debt To Equity Ratio dan Total Asset Turnover Terhadap Nilai Perusahaan Melalui Return On Equity Sebagai Variabel Intervening pada Perusahaan Farmasi yang Terdaftar di Bursa Efek Indonesia - Bagus Prabowo; Muis Fauzi Rambe (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research was conducted with the aim of testing and analyzing the influence of Debt to Equity and Total Assets Turnover on firm value through Return On Equity directly or indirectly. The population in this study were all pharmaceutical companies listed on the Indonesian Stock Exchange, while the sample that met the sampling criteria for observations was carried out for five years and there were six pharmaceutical companies listed on the Indonesian Stock Exchange. This research approach uses associative research. The data collection technique in this research uses documentation techniques and the analysis technique used is SEM (Structural Equation Model) analysis. The research results show that directly Debt to Equity Ratio, Total Assets Turnover, Return On Equity have no effect on firm value. Debt to Equity Ratio and Total Assets Turnover have no effect on Return On Equity. Indirectly, Return On Equity does not mediate the influence of Debt to Equity and Total Assets Turnover on firm value in pharmaceutical companies listed on the Indonesian Stock Exchange.